2017
DOI: 10.1038/srep46734
|View full text |Cite
|
Sign up to set email alerts
|

Size and shape variations of the bony components of sperm whale cochleae

Abstract: Several mass strandings of sperm whales occurred in the North Sea during January and February 2016. Twelve animals were necropsied and sampled around 48 h after their discovery on German coasts of Schleswig Holstein. The present study aims to explore the morphological variation of the primary sensory organ of sperm whales, the left and right auditory system, using high-resolution computerised tomography imaging. We performed a quantitative analysis of size and shape of cochleae using landmark-based geometric m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…We have shown that in human ossicles there is a rapid increase in mineralization during the first years of life [13]. There is also no evidence for relevant postnatal growth of the cochlear structures or ear ossicles with individual shapes [13,17]. This suggests a very early adaptation of the ossicular bone to its function, which persists throughout life.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…We have shown that in human ossicles there is a rapid increase in mineralization during the first years of life [13]. There is also no evidence for relevant postnatal growth of the cochlear structures or ear ossicles with individual shapes [13,17]. This suggests a very early adaptation of the ossicular bone to its function, which persists throughout life.…”
Section: Discussionmentioning
confidence: 77%
“…The auditory ossicles were taken from three sperm whales of 12, 13 and 15 years of age [16,17]. All specimens were transferred with special documentation of no commercial or trading interests according to the environmental authority of Schleswig-Holstein (Germany) and approved by the Institute for Terrestrial and Aquatic Wildlife Research (ITAW) on behalf of the Schleswig-Holstein Wadden Sea National Park.…”
Section: Materials and Methods (A) Specimensmentioning
confidence: 99%
“…This observation has been confirmed in many mammal groups (e.g. cetaceans 68 , 69 ; primates 70 ; primitive artiodactyls 71 ) except for sloths, which exhibit extremely slow locomotion 72 .Thus, the hypothetical specimen mean (consensus of all specimens from a species) was used for the phylogenetic test to not artificially decrease the homoplasy. The phylogenetic tree was created using Mesquite 3.04 software 73 .…”
Section: Methodsmentioning
confidence: 86%
“…More recent research on sperm whales is equivocal, with some studies illustrating little apparent characteristics of social structure of males 6 , 10 , 11 , 32 , while another recent study even showed that immature males form long-term relationships 33 . A recent study on size and shape variations of the bony components of sperm whale cochleae suggested already that individuals might be affiliated to different bachelor pods 34 . The present study assessed whether variations of the contamination profile are indicative of spatial aggregation (and putatively social structures) of young male sperm whales as they might reflect a variation in feeding preferences and/or in feeding grounds as diet is the main relevant exposure pathway for marine mammals 12 .…”
Section: Discussionmentioning
confidence: 99%